Tolerance of Gadget Use in Children as a Preventive Measure for Nomophobia - Ellen Prima, (International Journal of Scientific Research and Management (IJSRM), 2024)
Rapid developments in the field of science and technology have given birth to the phenomenon of "nomophobia", where people feel anxious and afraid if they cannot access their mobile phones. This also has an impact on children, where excessive use of gadgets can trigger negative behavior patterns and consumptive traits. In childhood, the brain develops rapidly and becomes the foundation for future activities and quality of life. Excessive use of gadgets in children can interfere with brain development and trigger behavioral changes. This study, with a qualitative method, examines the tolerance of gadget use in children as a preventive effort for nomophobia. From 20 child samples, it was found that four children were not addicted to gadgets and had good sleep quality, two children were not addicted to gadgets with poor sleep quality, two children were addicted to gadgets with poor sleep quality, and one child was addicted to gadgets with very poor sleep quality. These findings suggest that excessive use of gadgets can have a negative impact on children's sleep quality. Therefore, it is important for parents to limit the use of gadgets in children and encourage other activities that are more beneficial to their development.